Numerical study on harmful boundary of above-ground section leakage of natural gas pipeline. (December 2022) - Yu, Qiaoyan; Hou, Lei; Li, Yanhao; Chai, Chong; Liu, Jiaquan; Yang, Kai
Abstract: Natural gas has incomparable advantages compared with other energy, but the accidents caused by natural gas pipeline transportation cannot be ignored. In order to reduce the accident damage, it is necessary to master the concentration distribution of leaked gas in the atmosphere scientifically. The main contribution of this research is to predict the harmful boundary of gas diffusion. Numerical simulation was used to establish the leakage diffusion model of natural gas pipeline exposed to atmosphere. The influences of leakage rate, leakage diameter and wind speed on the harmful boundary of gas were studied. The results show that harmful boundary reaches a stable state after a period of leakage. Leakage rate and leakage diameter contribute to vertical height of harmful boundary, and have little effect in the horizontal direction. Wind speed is the main factor affecting gas diffusion path. Increasing wind speed results in decrease of vertical height and increase of horizontal distance of harmful boundary, gas diffusion develops near the ground in the downwind direction. The quantitative formula between harmful boundary of gas diffusion and influencing factors is proposed. This work has a great guiding significance for emergency rescue work in engineering. Highlights: Diffusion shape, diffusion path and flow field of gas leakage from pipeline are studied. Wind speed is the main factor affecting gas diffusion path. Leakage rate and leakage diameter contribute to vertical height of harmful boundary. Quantitative formula between harmful boundary and influencing factors is proposed.